Thiocyanate and Organic Carbon Inputs Drive Convergent Selection for Specific Autotrophic Afipia and Thiobacillus Strains Within Complex Microbiomes - Huddy, Robert J.; Sachdeva, Rohan; Kadzinga, Fadzai; Kantor, Rose S.; Harrison, Susan T. L.; Banfield, Jillian F. (Frontiers in Microbiology, 2021)
Thiocyanate (SCN-) contamination threatens aquatic ecosystems and pollutes vital fresh water supplies. SCN- degrading microbial consortia are commercially deployed for remediation, but the impact of organic amendments on selection within SCN- degrading microbial communities has not been investigated. Here, we tested whether specific strains capable of degrading SCN- could be reproducibly selected for based on SCN- loading and the presence or absence of added organic carbon. Complex microbial communities derived from those used to treat SCN- contaminated water were exposed to systematically increased input SCN concentrations in molasses-amended and -unamended reactors and in reactors switched to unamended conditions after establishing the active SCN- degrading consortium. Five experiments were conducted over 790 days and genome-resolved metagenomics was used to resolve community composition at the strain level. A single Thiobacillus strain proliferated in all reactors at high loadings. Despite the presence of many Rhizobiales strains, a single Afipia variant dominated the molasses-free reactor at moderately high loadings. This strain is predicted to breakdown SCN- using a novel thiocyanate dehydrogenase, oxidize resulting reduced sulfur, degrade product cyanate to ammonia and CO2 via cyanase, and fix CO2 via the Calvin-Benson-Bassham cycle. Removal of molasses from input feed solutions reproducibly led to dominance of this strain. . Although sustained by autotrophy, reactors without molasses did not stably degrade SCN- at high loading rates, perhaps due to loss of biofilm-associated niche diversity. Overall, convergence in environmental conditions led to convergence in the strain composition, although reactor history also impacted the trajectory of community compositional change.